Excess noise and other important characteristics of low light level imaging using charge multiplying CCDs. - Hynecek, J. (IEEE Transactions on electron devices)
This paper describes recent progress in technology of low light level image sensing using CCD sensors that multiply charge by impact ionization before its conversion into a voltage. The paper presents a brief description of the concept, the outline of a typical sensor design with some important details related to prevention of serial register blooming and achieving high dynamic range (DR), and then focuses primarily on the measurement and analysis of noise components that are important in these devices. The paper describes the theory of excess noise, shows the computation of the output signal probability distribution function (PDF), and the derivation of formula for the excess noise factor (ENF). Finally, it is concluded that under suitable conditions it is possible to achieve a single photon (electron) detection (SPD) performance.